1997
DOI: 10.1039/a606389f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of lower-valent molybdenum oxides in aqueous solutions by reducing Na2MoO4 with NaBH4

Abstract: Reduction of Na 2MoO 4 with NaBH 4 in aqueous solutions at ambient temperatures has been investigated systematically by varying the concentration and volume of NaBH 4 as well as the reaction pH. The reduction products have been characterized by X-ray diÂraction and diÂerential scanning calorimetry (DSC). The reduction yields metastable, amorphous oxides of lower-valent molybdenum, which crystallize around 350°C to give the binary oxide MoO 2 and the sodium molybdenum bronze Na 0.88 Mo 6 O 17 . The relative amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 7 publications
1
20
1
Order By: Relevance
“…2), indicating that the as-prepared samples are nanocrystalline and not amorphous. This is in contrast to the as-prepared samples in the molybdate and tungstate systems, which were found to be amorphous (22)(23)(24).…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…2), indicating that the as-prepared samples are nanocrystalline and not amorphous. This is in contrast to the as-prepared samples in the molybdate and tungstate systems, which were found to be amorphous (22)(23)(24).…”
Section: Resultscontrasting
confidence: 69%
“…Some of these binary oxides were found to be attractive as electrode materials for lithium batteries (20,21). A more systematic investigation of the molybdate (22,23) and tungstate (24), systems reveals that the volume and concentration of the borohydride, the reaction pH, and the degree of condensation of the metalate ions strongly influence the composition of the products. We report in this paper a systematic investigation of the reduction of KMnO with KBH in aqueous solutions with an aim to obtain manganese oxides.…”
Section: Which Is Generally Obtained Electrolytically (Emd) or By Chementioning
confidence: 98%
“…According to more recent studies, MoO 2 nanowires were electrodeposited reductively from an alkaline MoO 4 2À solution onto highly oriented pyrolytic graphite surfaces [16,17]. MoO [20,21]. The instability of the metastable dioxides with low valence states makes their synthesis difficult in solutions [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Manthiram et al (12,13) reported that, after a heat treatment at 623}773 K of the amorphous products formed by the reduction of K MoO in KBH solution, K MoO , K MoO , and K MoO were crystallized with MoO . We (14}17) also attained formerly by the solid state reactions a series of alkali metal bronzes containing small amounts of MoO by heating hydrated molybdenum bronzes in the neighborhood of 600 K in N atmosphere.…”
Section: Introductionmentioning
confidence: 99%